QUALITATIVE APPROACH IN DEVELOPING A TECHNOLOGY ACCEPTANCE MODEL FOR MOOCS IN MALAYSIAN HIGHER EDUCATIONAL INSTITUTIONS - Dr. Purushothaman Ravichandran, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Online teaching and learning is becoming more and more popular among Higher Educational Institutions and as a result of which teacher educators are expected to know good models of effective practices, which are required to assess the online teachers’ attainment. In this study, primary data collected through qualitative discussions were analyzed through the lens of online actives, in which, data gathered from 648 graduate teachers from 216 SMK schools in Perak were used. As one of the goals of the study is to assess and empower the teachers in online teaching and learning environment, the intentionality of the design of the work and the facilitation of the discourse throughout the work need to be modeled and facilitated by educators. As such, 10 teachers, were purposefully selected for the qualitative study from the sample size of 648 graduate teachers. Teachers’ journey through online integration was examined through the lens of three models, namely, Salmon’s 5 stage model, Technology Pedagogical Content Knowledge and Hooper and Rieber models, The outcome of this research paved way to teacher educators, who require technology acceptance models of how ICT can be appropriately integrated into rich teaching experiences for online integration of MOOCs.